2011
DOI: 10.1007/s11670-011-0074-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Chinese herbs decoction administration for management of hot flashes associated with endocrine therapy in breast cancer patients

Abstract: Objective: To evaluate the effect of Chinese herbs decoction Shu-Gan-Liang-Xue on endocrine therapyassociated hot flashes symptom in breast cancer patients.Methods: Sixty-six patients with breast cancer receiving adjuvant endocrine therapy were categorized to two groups, the control group received endocrine therapy alone, the other group is administered with Chinese herbs decoction Shu-Gan-Liang-Xue besides the endocrine therapy: Shu-Gan-Liang-Xue decoction was administered above 6 months per year for more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Specifically, guarana and Ganoderma lucidum may be beneficial in treating fatigue amongst breast cancer patients (40,45) whereas QOL may be improved by use of Ganoderma lucidum, essiac, and Chinese medicinal herbal mixtures including YZDS and THL-P (33,34,38,40). Another Chinese medicinal herbal mixture, Shu-gan-liang-xue may also be beneficial in alleviating menopausal symptoms (35). There is also some evidence to suggest glutamine supplementation may be beneficial in the treatment of oral mucositis in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Specifically, guarana and Ganoderma lucidum may be beneficial in treating fatigue amongst breast cancer patients (40,45) whereas QOL may be improved by use of Ganoderma lucidum, essiac, and Chinese medicinal herbal mixtures including YZDS and THL-P (33,34,38,40). Another Chinese medicinal herbal mixture, Shu-gan-liang-xue may also be beneficial in alleviating menopausal symptoms (35). There is also some evidence to suggest glutamine supplementation may be beneficial in the treatment of oral mucositis in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zhuang et al (2012) found no significant improvement in treatment toxicity symptoms between RG-CMH and placebo group (P > 0.05) (36). Two studies were of neutral quality (33,36), whereas the other 2 were rated negative quality (34,35).…”
Section: Chinese Herbal Medicine Mixturesmentioning
confidence: 95%
See 3 more Smart Citations